Creating and Maintaining Database - Miranda Arguedas, Alice (1992)
In the cycle of Professional Conferences the M.L.S. Alice Miranda of the School of Libraries, Documentation and Information of the National University of Costa Rica presents her paper with the theme "The Management of Information in Specialized Areas in Costa Rica".